Room-temperature intrinsic ferromagnetism in epitaxial CrTe2 ultrathin films - Xiaoqian Zhang (Nature Portfolio, 2021)
The emergence of two dimensional ferromagnetism suffers from an inherent fragility to thermal fluctuations, which typically restricts the Curie temperature to below room temperature. Here, Zhang et al present CrTe2 thin films grown via molecular beam epitaxy with a Curie temperature exceeding 300 K.